Contributions of Working Conditions on Performance of Secondary School Teachers in Moshi District Council, Tanzania - Esther S. Ngereza; Dr. Hezron Onyancha; Prof. Evans Okendo Ogoti, (Indian Journal of Management and Language (IJML), 2025)
This study was aimed at assessing the contribution of working conditions on work performance of public secondary school teachers in Moshi District, Tanzania. The Two Factor Theory by Herzberg (1959) was used in explaining about specific work motivation that bring about job satisfaction. The study used a convergent research design with a mixed research approach. The population of the study included 1,145 public secondary school teachers from which a sample of 256 respondents was obtained. 5 heads of schools and 3 Ward education Coordinators were used as key informants for the study. Data was collected by using a questionnaire and a key informant interview guide. The validation of the instrument was done through a research expert from MWECAU, and the reliability of the instrument was ensured through Cronbach alpha. The reliability for teachers was r= (0.8). Quantitative data was analyzed using descriptive statistics to get frequencies, percentages and means. Qualitative data was analyzed using contextual themes analysis and narrative analysis methods. Findings indicated that working conditions of secondary school teachers have a positive impact on their performance. The study concluded that working condition in public secondary schools have highly impact on teachers working performance. The study recommends that Ward Education Coordinators should regularly assess the working conditions and resource needs of schools within their jurisdiction.